Effect of Infiltration Pressure on Thermal Conductivity of Al 2014 Matrix Composite Powered by Silicon Carbide - Ates, Serkan; Uzun, Ibrahim; Calin, Recep; Citak, Ramazan (Asian Journal of Chemistry, 2011)
By using pressure infiltration method, metal matrix composites are produced by saturating Al 2014 aluminum composite to the gaps among SiC powders. SiC powders filled into stainless steel tubes are fastened between the filters conducting only liquid material, dipped into pressurized molten boiler and infiltrated in 3 min under 500-900 kPa pressures at 750 ºC. The image analyses of samples were done by scanning electron microscope (SEM). Densities, porosities and thermal conductivities of them were identified experimentally. It is defined that by the increase of infiltration pressure, porosity amount decreases but the value of thermal conductivity increases.